Implementing an application security program. (Manning Publications, 2023)
The Application Security Program course teaches you to implement a robust program of security throughout your development process. It goes well beyond the basics, detailing flexible security fundamentals that can adapt and evolve to new and emerging threats. Its service-oriented approach is perfectly suited to the fast pace of modern development. Your team will quickly switch from viewing security as a chore to seeing it as an essential part of their daily work. Follow the expert advice in this guide and you'll reliably deliver software that is free from security defects and critical vulnerabilities.